Hypocalcemic Seizures in Infancy and its Relationship with Maternal Vitamin D Deficiency - Biswas, Rabi; Hasan, ABM Kamrul (Dhaka Shishu (Children) Hospital Journal, 2022)
Background: Hypocalcemia accounts for a large number of seizures in infants presented at the emergency department of our hospital. Objective: To evaluate the role of Vitamin D deficiency as the etiology of hypocalcemic seizures in infancy and its relationship with maternal Vitamin D levels. Methods: Cross sectional hospital based study over a period of 35 months from July 2016 to June 2019. Total 60 infants with hypocalcemic seizures were enrolled into the study. Blood samples were taken for serum total calcium, inorganic phosphate, alkaline phosphatase, albumin, 25(OH)D and PTH from the child. Maternal serum 25(OH)D levels were measured as well. Results: The mean age of the studied infants was 3.6 (±1.2) months. All patients had low total calcium (mean 6.5 mg/dl) and most of them had low inorganic phosphate (mean 3.5 mg/dl), while all of them had raised alkaline phosphatase (mean 1093.50 IU/L) and PTH levels (mean104 pg/ml) at presentation. Forty percent of infants were severely deficient and 60% were deficient in vitamin D; none of them were vitamin D sufficient. Among their mothers, none were sufficient, 10% were insufficient, 45% were deficient, and 45% were severe deficient of vitamin D. Neonatal 25(OH)D showed strong negative correlation with their serum PTH levels and strong positive correlations with maternal serum 25(OH)D levels. Conclusion: All infants in our setting presented with hypocalcemic seizures were found due to Vitamin D deficiency and it was mostly related to maternal Vitamin D deficiency. DS (Child) H J 2021; 37(2): 98-102